Zwischen Proposition und Erlebnis. Zum Erkenntnisbegriff der Lyrik aus philosophischer Sicht - Christiane Schildknecht (Internationale Zeitschrift für Kulturkomparatistik, 2019)
From the point of view of a philosophy of literature the position of lyric poetry is specific. While epistemic approaches focus on fiction and its forms of cognition, lyric poetry is often reduced to conveying emotions or atmosphere. While arguing for the epistemic content of lyric poetry, the paper will focus on the concept of representation (‚Vergegenwärtigung‘). Emphasis will be placed on the non-propositional component of cognition as well as on a specific understanding of experience in the form of knowing, ‘what-it-islike’. While didactic poetry displays a propositional character, nonsense-poetry with its emphasis on analogy as well as the poetry of experience (‚Erlebnisdichtung‘) fall on the non-propositional side. The form of cognition that is central, here, resembles that of Bertrand Russell’s ‘knowledge by acquaintance’, albeit as one of indirect acquaintance. In contrast to phenomenal experience and an emotivistic reading of poetry the non propositional knowledge it conveys is based on cognitive procedures such as imagination and/or projection. In sum, then, the epistemic impact of literature is not restricted to fiction but can also be said to apply to lyric poetry.